PENGARUH STRES KERJA TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT. NURANY JAYA TOUR & TRAVEL SAMARINDA - Dwi Ariyanti (OBOR: Oikonomia Borneo, 2019)
The research problem formulation is whether work stress has a significant effect on organizational commitment to employees of PT. Nurany Jaya Tour & Travel Samarinda. The purpose of this study was to determine the effect of work stress on organizational commitment to employees of PT. Nurany Jaya Tour & Travel Samarinda. This research method is associative using statistical analysis tools with the help of SPSS ver 24 computer program to determine the effect of each variable. From the results of the analysis, it is known that the value of Simple Linear Regression is Y = 3.077 + 0.198, this indicates that work stress has a positive effect on organizational commitment. As for the results of the Coefficient of Determination analysis, it is known that R2 = 0.042, this shows that there is an influence of 4.2% between Job Stress and Organizational Commitment. And based on the results of the F test, it is known that the significant value (sig) is 0.202> 0.05 and the Fcount is 1.682>Ftable 4.10. From these results, H0 is accepted and H1 is rejected, which means that there is no significant effect between Work Stress (X) together on Organizational Commitment (Y) Employees at PT. Nurany Jaya Tour & Travel Samarinda